2012
DOI: 10.1371/journal.pone.0041361
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA Methylation in Purified Human Blood Cells: Implications for Cell Lineage and Studies on Disease Susceptibility

Abstract: Methylation of cytosines at CpG sites is a common epigenetic DNA modification that can be measured by a large number of methods, now even in a genome-wide manner for hundreds of thousands of sites. The application of DNA methylation analysis is becoming widely popular in complex disorders, for example, to understand part of the “missing heritability”. The DNA samples most readily available for methylation studies are derived from whole blood. However, blood consists of many functionally and developmentally dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
1,065
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 908 publications
(1,104 citation statements)
references
References 46 publications
17
1,065
1
3
Order By: Relevance
“…30 Interrogating our Illumina 27K data by the algorithm introduced by Houseman et al, 29 we found significantly higher granulocytes proportion in BC patients than in controls (68.…”
Section: Resultsmentioning
confidence: 81%
“…30 Interrogating our Illumina 27K data by the algorithm introduced by Houseman et al, 29 we found significantly higher granulocytes proportion in BC patients than in controls (68.…”
Section: Resultsmentioning
confidence: 81%
“…In the analysis, we controlled for the following covariates a priori based on the relevant literature: 6,19,26,27 total PM 2.5 mass, cell proportions (CD4 C T lymphocytes, CD8 C T lymphocytes, natural killer cells, B cells, monocytes) estimated by the Houseman et al method, [28][29][30] age, body mass index [BMI, computed as weight (in kilograms) divided by height (in square meters)], cigarette pack years, smoking status (never, ever), alcohol consumption ( 2 drinks/day, < 2 drinks/day), years of education, year and season (spring: March-May, summer: June-August, fall: September-November, winter: December-February). Potential batch effects were also considered, including plate, the position of the chip on plate, and the row and column position on the chip.…”
Section: Resultsmentioning
confidence: 99%
“…Mucus production and white blood cell count decrease substantially with time, but it remains important to exclude urine samples with substantial contamination in order to measure the correct population of cells in analyzing DNA methylation changes in the neobladder. In our study, we used tissue-specific DNA methylation loci as surrogate markers to confirm the identity of the cell population collected from the neobladder urine sediments (Houseman et al 2012;Reinius et al 2012). We have previously generated Infinium HumanMethylation27 data for normal blood, small intestine, and bladder, from which we identified inflammatory cell-specific probes which are specifically unmethylated in white blood cells and methylated in normal small intestine and urothelium (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%